2020
DOI: 10.31234/osf.io/7udy4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does sharing memories make us feel closer? The roles of memory type and culture

Abstract: The present study investigated in a cross-cultural context whether sharing different types of memories would differentially influence perceived relationship closeness and how that, in turn, was related to psychological well-being. Participants (N = 410) from European American and Asian cultural backgrounds reported their feelings of closeness to a conversational partner in hypothetical scenarios following five types of information sharing: specific and general autobiographical memories, specific and general vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…General memory research has shown that people share memories for various purposes: to convey information about who they arethe self function, to entertain others and develop and maintain relationshipsthe social function, to seek empathy and support for emotion regulation and copingthe therapeutic function, and to impart lessons to help othersthe directive function (e.g., Alea and Bluck 2003;Kulkofsky et al 2010;Pillemer 2001). In particular, social connection is the most prominent purpose of fact-to-face memory sharing (Alea and Bluck 2003;Guan and Wang 2020;Kulkofsky et al 2010). In the context of social media, people share memories for similar reasons (Hollenbaugh 2011;Wang 2013).…”
Section: The Represented Self and Its Externalisationmentioning
confidence: 99%
“…General memory research has shown that people share memories for various purposes: to convey information about who they arethe self function, to entertain others and develop and maintain relationshipsthe social function, to seek empathy and support for emotion regulation and copingthe therapeutic function, and to impart lessons to help othersthe directive function (e.g., Alea and Bluck 2003;Kulkofsky et al 2010;Pillemer 2001). In particular, social connection is the most prominent purpose of fact-to-face memory sharing (Alea and Bluck 2003;Guan and Wang 2020;Kulkofsky et al 2010). In the context of social media, people share memories for similar reasons (Hollenbaugh 2011;Wang 2013).…”
Section: The Represented Self and Its Externalisationmentioning
confidence: 99%
“…It has been established that memory sharing is one of the primary functions of autobiographical memory [40]. Sharing autobiographical memories has been shown to lead to relationship closeness across cultural settings [41]. It is, therefore, a critical omission in the memory function literature that the role of different interlocutors is rarely considered.…”
Section: Studymentioning
confidence: 99%
“…As alluded to, autobiographical memory researchers theorise that reminiscing is a tool to maintain relationships (Alea & Bluck, 2003). A study by Guan and Wang (2022) provides empirical evidence for this theory. They asked participants to report how close they felt to an imagined conversation partner after reading either some of their autobiographical memories, vicarious memories (i.e., a third party's personal memories), or impersonal information.…”
Section: Theorised Predictor Similaritiesmentioning
confidence: 99%
“…Similarly, when parents elaboratively reminisce (reminiscing that encourages the child's recall) with their children, it encourages secure attachment (Chae et al, 2011;Fivush, 2007). Adults in close relationships also discuss memories in ways that craft a shared sense of reality, promoting closeness (Guan & Wang, 2022;Hardin & Higgins, 1996;McLean & Pasupathi, 2011;Rossignac-Milon & Higgins, 2018). Correlational evidence suggests that closeness and social support are strongly positively related (Campos et al, 2014;Crocker & Canevello, 2008;Priel et al, 1998).…”
Section: Functional Similarities Between Social Reminiscing and Emoti...mentioning
confidence: 99%
See 1 more Smart Citation